2017
DOI: 10.5080/u22702
|View full text |Cite
|
Sign up to set email alerts
|

L-Arginine Add-On Treatment for Schizophrenia: A Randomized, Double-Blind, Placebo-Controlled, Crossover Study

Abstract: ÖZETAmaç: Şizofrenide mevcut ilaç tedavileri kısmen etkili olduğundan güçlendirme veya kombinasyon tedavileri sık olarak uygulanmaktadır. Nitrik oksitin (NO) şizofreninin fizyopatolojisinde rol oynadığı öne sürülmektedir. L-arjinin NO öncülü olan bir esansiyel aminoasittir. Bu çalışmada şizofreni veya şizoafektif bozukluk tanısı konmuş klinik belirtileri kısmen devam eden hastaların mevcut tedavilerine eklenen L-arjinin'in, şizofreninin pozitif, negatif ve depresif belirtileri üzerindeki etkisinin incelemesi a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Conversely, SNP was unable to express an antipsychotic profile in clinical trials in which patients were older, cigarette smokers, presenting less serious negative symptoms and with longer disease course respect to the studies in which the efficacy of SNP was revealed [ 60 , 61 , 62 , 63 ]. The role of nicotine as a critical factor of the ineffectiveness of SNP should also be considered since it interferes with NO and reduces SNP efficacy [ 64 ]. It can be thus hypothesized that SNP seem to improve schizophrenia symptoms when is administered in young patients, no smokers and having a short history of the disease.…”
Section: Snp and Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, SNP was unable to express an antipsychotic profile in clinical trials in which patients were older, cigarette smokers, presenting less serious negative symptoms and with longer disease course respect to the studies in which the efficacy of SNP was revealed [ 60 , 61 , 62 , 63 ]. The role of nicotine as a critical factor of the ineffectiveness of SNP should also be considered since it interferes with NO and reduces SNP efficacy [ 64 ]. It can be thus hypothesized that SNP seem to improve schizophrenia symptoms when is administered in young patients, no smokers and having a short history of the disease.…”
Section: Snp and Schizophreniamentioning
confidence: 99%
“…There is scant evidence concerning the clinical efficacy of other NO modulators in schizophrenia and the results reported are contradictory. Specifically, in randomized, double-blind, placebo-controlled studies either the NO precursor L-arginine (repeatedly administered in patients under medication) [ 64 ] or the NO donor glyceryl trinitrate (GTN) (chronically administered in first-episode unmedicated patients) [ 65 ] failed to improve schizophrenia symptoms. Both studies were conducted in a small size of participants and only one dose of compound was used.…”
Section: Snp and Schizophreniamentioning
confidence: 99%
“…Âûÿâëÿåìûå èçìåíåíèÿ â àìèíîêèñëîòíîì ñïåêòðå ñîçäàþò ïðåäïîñûëêè äëÿ ðàçâèòèÿ íîâûõ ïåðñïåêòèâíûõ òåðàïåâòè÷åñêèõ ñòðàòåãèé â ïëàíå ïðèìåíåíèÿ â òåðàïèè ïñèõè÷åñêèõ ðàññòðîéñòâ àìèíîêèñëîò èëè ïðåïàðàòîâ, âîçäåéñòâóþùèõ íà èõ ìåòàáîëèçì [54][55][56][57][58][59][60].…”
Section: перспективы применения аминокислот ацилкарнитинов и препараunclassified
“…Importantly, this triple application, L-NAME vs. L-arginine vs. combination [ 8 ], would markedly overwhelm the regular level in the corresponding NO-studies, the application of the one single NO-agent (i.e., L-NAME) (i.e., for review, see [ 4 ]). Evidently, as demonstrated with the “positive-like” schizophrenia models’ symptoms [ 8 ], the triple application would better define the whole NO-system complexity (otherwise, the successful use of either NOS-blocker [ 12 , 29 , 30 ] or L-arginine [ 31 , 32 ] might disable each other value in the schizophrenia therapy [ 12 , 29 , 30 , 31 , 32 ]). This might be the case despite the fact that the neurobiology of the positive symptoms (i.e., mesolimbic pathways that involve dopamine and glutamate networks) is distinct from that of negative symptoms (i.e., fronto-cortical temporal and cortico-striatal pathways) [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%